MODELING OF ELECTRON TRANSMITTANCE AND LEAKAGE CURRENT IN AN ISOTROPIC MOS CAPASITOR BY USING AN AIRY WAVEFUNCTION-APPROACH - (NIM : 20212018), KHAIRIAH
A model of electron transmittance and leakage current in an isotropic metal-oxidesemiconductor (MOS) capacitor with a high-k material has been developed by considering the coupling effect between transverse and longitudinal kinetic energies of an electron which is represented by an electron phase velocity in the gate. The structure of n+Poly-Si/HfSiOxN (high-kmaterial)/Trap/SiO2/Si was applied to calculate the transmittance and leakage current The main problems in the use of high-k material is the charge trapping formed at the high-k material/SiO2 interfaces. Therefore, it becomes important to model the transmittance and leakage current by considering the effect of charge trapping. The transmittance was derived by employing the Airy wavefunction-approach, and the obtained transmittance was then used to calculate the leakage current for various electron phase velocities, depths and widths of trap, incident angles of electron and thicknesses of HfSiOxN. The calculated results show that the transmittance and leakage current increases as the electron velocity decreases and reach the highest values when they were calculated without coupling effect. It is also shown that the transmittance and leakage current enhance as the depth and width of trap get deeper and wider, respectively The electron movement becomes easier when the electron tunnels the barrier perpendicular to the interface. In addition, the leakage current increases with decreasing the HfSiOxN thickness.